Membangun Server Private Cloud Storage pada Dinas Komunikasi Informasi Statistik dan Persandian Kabupaten Lebong - Muhammad Al Aziz; Khairil Khairil; Sapri Sapri (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2022)
Lebong Regency Statistical Information Communication and Encryption Office is one of the Government Agencies which located in Lebong Regency. So far, the processing and archiving data at Statistical Information Communication and Encryption Office, Lebong Regency, has utilized applications on the computer, namely  Office Application Package. Data processing, typing, or archiving are still carried out on their laptops/computers, so if you want to share data with other employees, you must use additional media, namely flash drives or external hard drives and also email. In addition, several employees have used document archive storage in cloud storage using Google Drive. The implementation of private cloud storage at Statistical Information Communication and Encryption Office, Lebong Regency used Owncloud Server through NDLC (Network Development Life Cycle) research method approach to facilitate document/archive storage and can also simplify the process of sending documents/archives to other employees, and can be accessed anytime and anywhere via the internet. Owncloud server storage that is built is 1 TeraByte so that each user will get an average storage capacity of 20-50 GB. Based on the results of the tests that have been carried out, it can be concluded that the functionality of private cloud storage using owncloud server makes it easier for employees to carry out data processing and archiving in a structured manner. Private cloud storage can be accessed offline or online via the internet, making it easier for employees who work from home to access work data. In addition, by building private cloud storage independently, the need for the amount of storage can be adjusted because it is scalable.